Carta de Adolfo Porrata Doria a Benigno Fernández García - Porrata Doria, Adolfo; Fernández García, Benigno (My University, 1934)
Contratiempo en el asunto de Manuel A. Martínez Dávila.
Keywords: Martínez Dávila, Manuel A.,1883-1934; Iglesias, Samalea; Fonalledas Córdova, Gerardo